2018
DOI: 10.1038/s41467-018-04558-1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying gene targets for brain-related traits using transcriptomic and methylomic data from blood

Abstract: Understanding the difference in genetic regulation of gene expression between brain and blood is important for discovering genes for brain-related traits and disorders. Here, we estimate the correlation of genetic effects at the top-associated cis-expression or -DNA methylation (DNAm) quantitative trait loci (cis-eQTLs or cis-mQTLs) between brain and blood (rb). Using publicly available data, we find that genetic effects at the top cis-eQTLs or mQTLs are highly correlated between independent brain and blood sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
300
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 315 publications
(335 citation statements)
references
References 63 publications
14
300
0
Order By: Relevance
“…In addition, as in TWAS, we could apply our method to and then combine the results from multiple tissues, or apply other more powerful and adaptive tests (Gusev et al 2016;Xu et al 2017). The issue with the choice of the tissue or cell type is similar to that in TWAS: a recent study (Qi et al 2018) has shown that, for brain-related traits, using blood cis-eQTL (with larger sample sizes) could gain power over using (smaller) brain eQTL data sets, while the genetic effects of cis-eQTL are highly correlated between independent brain and blood samples. Finally, although our application was focused on schizophrenia, the proposed method is quite general and applicable to other traits based on either individual-level or summary GWAS data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as in TWAS, we could apply our method to and then combine the results from multiple tissues, or apply other more powerful and adaptive tests (Gusev et al 2016;Xu et al 2017). The issue with the choice of the tissue or cell type is similar to that in TWAS: a recent study (Qi et al 2018) has shown that, for brain-related traits, using blood cis-eQTL (with larger sample sizes) could gain power over using (smaller) brain eQTL data sets, while the genetic effects of cis-eQTL are highly correlated between independent brain and blood samples. Finally, although our application was focused on schizophrenia, the proposed method is quite general and applicable to other traits based on either individual-level or summary GWAS data.…”
Section: Discussionmentioning
confidence: 99%
“…To search for evidence of the functional effects of genetic variants associated with any of the three sedentary traits, we used multiple functional eQTL mapping. This was done using summary data based Mendelian randomization (SMR) 58 analysis (version 0.710) in data repositories from GTEx V7 59 , GTEx brain 60 , Brain-eMeta eQTL 60 and blood eQTL from Westra 61 and CAGE 62 . EQTL genes were considered as a candidate causal gene if they achieved a Bonferronicorrected significance of P < 0.05/187,747 = 2.66 × 10 −7 , passed the HEIDI test of P > 0.05 and if the lead variants of the eQTL genes were in LD (R 2 > 0.8) with the queried variants.…”
Section: Methodsmentioning
confidence: 99%
“…This strategy would have missed genes with a cis-eQTL effect in retina but not in blood. However, we considered that if cis-eQTL effects are similar across tissues 18,24 , using a blood eQTL data set of large sample size could increase the power of gene discovery in comparison to using a retina eQTL data set of small sample size. In addition, blood is much more accessible than retina so that the growth of eQTL data from blood is expected to be faster than that from retina, suggesting that the power of our analysis strategy could be substantially improved in the future by leveraging blood eQTL data sets with sample sizes of orders of magnitude larger than that used in this study 35 .…”
Section: Discussionmentioning
confidence: 99%